Structural characteristics of a neutral Glycyrrhiza uralensis polysaccharide and its fermentation properties on the gut microbiota of immunocompromised rats in vivo and vitro - Sun, Jie; Wu, Yi-Xuan; Li, Xin-Li; Xie, Wen-Jie; Xiong, Qing-Ping; Jiang, Chang-Xing; Tang, Shu-Wan; Peng, Guo-Ping; Zheng, Yun-Feng (Frontiers in Nutrition, 2025)
Glycyrrhiza polysaccharides (GPs) exhibit notable physiological activity; however, their structure is not well understood. The novel neutral polysaccharide fraction GP-1 was isolated from the roots and rhizomes of Glycyrrhiza uralensis Fisch. The fermentation properties of GP-1 were investigated in vitro and in vivo in immunocompromised rats. The molecular weight (Mw) of GP-1 is 7.6 kDa. The analysis of the monosaccharide composition indicated that GP-1 is a glucan. Nuclear magnetic resonance spectroscopy and methylation analyses revealed that GP-1 comprised a glucan main chain linked by α-D-Glcp-(1 → 4) bonds, with β-D-Glcp-(1 → 6)-α-D-Glcp-(1 → side branches at the C-6 position of 1,4,6-Glc and β-D-Glcp-(1 → side branches at the C-3 position of 1,3,4-Glc. Staining with Congo red confirmed the presence of a triple-helix structure. Scanning electron microscopy revealed that GP-1 has granular morphology. Pharmacological studies showed that GPs and GP-1 modulated the balance of the gut microbiota and influenced the production of short-chain fatty acids. In addition, the in vivo fermentation of GP and the in vitro fermentation of GP-1 promoted the growth of certain probiotics, particularly Lactobacillus and Dubosiella. These results underscore the structural characteristics of GP-1 and its potential as a prebiotic agent.